A human rights-based framework to assess gender equality in health systems: the example of Zika virus in the Americas - Carol Vlassoff; Ronald St. John (Taylor & Francis Group, 2018)
Background: The right to health was enshrined in the constitution of the World Health Organization (WHO) in 1946 and in the Universal Declaration of Human Rights in 1948. The latter Declaration, which also guaranteed women's rights, was signed by almost all countries in the world. Subsequent international conventions reinforced these rights, requiring that women be able to realize their fundamental freedoms and dignity. Although the value of incorporating gender into health systems has been increasingly acknowledged over the years, gender inequalities in health persist. Objective: To introduce a tool to help countries assess their performance in addressing gender inequalities in their health systems, using the example of the Zika virus (ZIKV) in countries of the Americas. Methods: This paper is based on comprehensive reviews of the literature on the links between gender equality, health systems and human rights, and available scientific evidence about an adequate response to ZIKV. Results: The authors present a simple two-part framework from the human rights perspectives of the health system as duty bearer, incorporating WHO's six health system building blocks, and of its clients as rights holders. The authors apply the framework to ZIKV in the Americas, and identify strengths and weaknesses at every level of the health system. They find that when considering gender, health systems have focused mainly on dichotomous sex differences, failing to consider broader gender relations and processes affecting access to services, quality of care, and health outcomes. Conclusions: The authors' framework will permit countries to assess progress toward gender equality in health, within the context of their human rights commitments, by examining each health system building block, and the degree to which clients are realizing their rights. By applying the framework to specific health conditions, gender-related achievements and shortcomings can be identified in each health system component, fostering a more comprehensive and gender-sensitive response.